MODELING PROPERTIES OF BLOCKBOARDS MADE OF POST-CONSUMER WOOD ON THE BASIS OF THE FINITE ELEMENT METHOD - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2015)
An approach has been proposed to predict properties of blockboards made of Post-consumer wood by using the finite element method. A model of physical and mechanical properties of PCW strips has been proposed using finite-element analysis of blockboards based on cylindrical coordinate system of the anisotropy of constant elasticity. Substantiation of new design of PCW-made blockboard which is based on the use of the system of finite element analysis allows to identify the shortcomings of these products at the conceptual stage of the project and correct them before fabrication according to the given engineering specifications. The proposed optimal pattern of layout of annual layers in adjacent strips of PCW-made blockboards, which provides improved shape stability (reduced warpage) of the design while reducing stress arising from the increasing moisture content of the product in the process of operation. Mathematical models that predict (describe) the strength and shape stability of PCW-made blockboards have been proposed. The developed model can be applied to study and optimize new designs of blockboard in terms of strength and deformability